The role of human property administration in quality management in the public sector - Gogalis, Theodoros (International Conference on Business and Economics - Hellenic Open University, 2023)
Human Resource Management is defined as "The design, implementation and maintenance of strategies to manage people for optimum organization performance where they work". It constitutes a set of strategies to be implemented in the public sector so that its operations could give high quality services and satisfaction to the citizens. This paper deals with the role and importance of human resource management in creating an efficient and functionally sound Greek public sector. An attempt is made to analyze the importance of Human Resource Management in the operation and development of public bodies through its connection to the Common Evaluation Framework which is essentially a "new" tool for Total Quality Management and which has been the subject of research by many scholars. It is apparent the lack of adoption of quality management principles and the lack of a culture of change which leads to reduced efficiency of public services and its human resources. This combined by the lack of implementation of modern Total Quality Management practices with due emphasis on skills, employee training, performance appraisal, communication and labor relations. The present research has shown that it is imperative to upgrade the human resource management strategies implemented in the public sector of our country through the broader and more effective implementation of the principles of human resource management in order to both enhance employee performance and effective functioning of the public sector. Keywords: human resources management, total quality management, management practices, public sector.